2020
DOI: 10.3390/diagnostics10020113
|View full text |Cite
|
Sign up to set email alerts
|

Urinary MicroRNA-21-5p as Potential Biomarker of Interstitial Fibrosis and Tubular Atrophy (IFTA) in Kidney Transplant Recipients

Abstract: Chronic renal allograft dysfunction (CAD) is a major limiting factor of long-term graft survival. The hallmarks of progressive CAD are interstitial fibrosis and tubular atrophy (IFTA). MicroRNAs are small, regulatory RNAs involved in many immunological processes. In particular, microRNA-21-5p (miR-21) is considered to be strongly associated with pathogenesis regarding tubulointerstitium. The aim of this study was to assess urinary miR-21 expression levels in the kidney transplant recipients and determine their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…It has been well documented that miR‐21 is involved in fibrosis of the kidneys and other organs, including the heart, 21 liver 22 and lungs 23 . According to previously published studies, 24,25 the miR‐21 level is increased in renal fibrosis tissue and serves as an important biomarker of fibrosis in plasma 26 and urinary tissue 27 . Ample evidence supports miR‐21 as a promoting factor during renal fibrosis, and targeting miR‐21 likely has a therapeutic effect and attenuates renal fibrosis development 28,29 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been well documented that miR‐21 is involved in fibrosis of the kidneys and other organs, including the heart, 21 liver 22 and lungs 23 . According to previously published studies, 24,25 the miR‐21 level is increased in renal fibrosis tissue and serves as an important biomarker of fibrosis in plasma 26 and urinary tissue 27 . Ample evidence supports miR‐21 as a promoting factor during renal fibrosis, and targeting miR‐21 likely has a therapeutic effect and attenuates renal fibrosis development 28,29 .…”
Section: Discussionmentioning
confidence: 98%
“… 23 According to previously published studies, 24 , 25 the miR‐21 level is increased in renal fibrosis tissue and serves as an important biomarker of fibrosis in plasma 26 and urinary tissue. 27 Ample evidence supports miR‐21 as a promoting factor during renal fibrosis, and targeting miR‐21 likely has a therapeutic effect and attenuates renal fibrosis development. 28 , 29 In our study, after ligation of the left ureter for 7 and 14 days, the morphology of obstructed kidneys changed dramatically.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, another miRNome study of uEV from donors reported that the profile of miRNA did not discriminate between living donors and deceased donors before transplantation [ 62 ]. The role of miRNA in uEV after kidney transplantation is not yet fully explored as currently most diagnostic findings of miRNA are based on human kidney disease before transplantation [ 59 ], cultured kidney cell [ 30 , 63 ], animal model [ 63 , 64 ], or urine sample only with no uEV isolation or detection [ 57 , 65 , 66 , 67 , 68 ], rather than on uEV from KTR after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…However, uEV-miRNA might be a major localization/derivation of total urinary miRNA [ 57 ], where urinary miR-21 is especially highlighted during kidney transplantation. Compared to a group with normal function, KTR with IFTA showed upregulated urinary miR-21 [ 65 ], which corresponded to elevated uEV-miR-21 during chronic kidney disease [ 63 ]. Khalid et al reported that elevated urinary miR-21 could predict DGF with an AUC between 0.75 to 0.94 [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that urinary miR-21 level may have prognostic value in hypertensive kidney injury 9 , 39 and kidney allograft recipients. 40 , 41 …”
Section: Discussionmentioning
confidence: 99%